Performance of Analog Network Coding Based Two-Way EH Relay With Beamforming - Modem, Sudhakar; Prakriya, Shankar (IEEE transactions on communications, 2017)
In this paper, we investigate the performance of an analog network coding based two-way relay system with multiple-antenna source terminals and single-antenna energy harvesting (EH) relay. We consider time-switching relaying protocol to perform EH and information processing at the amplify and forward EH relay. Assuming that the multiple-antenna source with a better link beamforms energy to the relay, we derive expressions for the system outage, ergodic sum-rate, and sum symbol error rate. In the analysis, we take into account the sensitivity of the energy harvesting circuit. We investigate the problem of throughput maximization by optimizing the fraction α of time spent on EH, and derive closed-form expressions for optimum α in important special cases. We analyze the problem of relay location for fixed α, and show that the optimum location varies with source terminal antennas. We further show that joint optimization of relay location and α yields best throughput performance. We show through simulations that unlike throughput, the optimum α that maximizes the ergodic sum-rate does not show much variation with system parameters. Simulation results with practical parameter values demonstrate the accuracy of the derived analytical expressions.